Method for controlling large-size inclusions in silicon-aluminum deoxidized steel

By combining the BOF-LF-RH-CC process with slag removal and the use of highly reducing slag, the oxidizing and reactivity of refining slag are controlled, solving the problem of controlling large-sized inclusions in silicon-aluminum deoxidized steel and achieving product production with a low scrap rate.

CN121450877APending Publication Date: 2026-02-03ZENITH STEEL GROUP CORP CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511749495.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-26
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

Existing technologies are insufficient to effectively control large inclusions in silicon-aluminum deoxidized steel, resulting in a high product scrap rate. In particular, the proportion of low-melting-point CaO-containing inclusions is high, and it is difficult to suppress slag entrapment in refining slag.

Method used

The BOF-LF-RH-CC process is adopted, which combines slag removal process and high-reducibility pre-melted refining slag to control the oxidizing and reactivity of refining slag. The risk of inclusion and slag entrapment is reduced by SiC deoxidation, argon stirring and molten steel settling. Iron sheet is used to cover the immersion pipe opening to ensure that no slag is entrapped during the immersion process.

Benefits of technology

It significantly reduced the product scrap rate caused by large inclusions to less than 2%, reaching the advanced level in China and improving the stability of product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

The invention belongs to the technical field of steelmaking, and relates to a method for controlling large-size inclusions in silicon-aluminum deoxidized steel. Converter tapping adopts a silicon-aluminum deoxidation process, after tapping, high-oxidability slag is removed by adopting a slagging-off process, and then high-reducibility premelting refining slag is added for re-slagging, so that the slag (TFe + MnO) at most of the refining moments is maintained within 0.50%; in the refining process, the stirring strength is controlled to control the desulfurization rate of the refining slag within 50%, so that the slag entrapment degree of the refining slag is reduced to the maximum extent; two iron sheets with the thickness being 2 mm are placed on the liquid level of the slag in advance before RH vacuum treatment, it is guaranteed that the slag is prevented from being drawn into the dip pipe in the process that the dip pipe is inserted into the molten steel, soft blowing is conducted for 10-15 min after RH vacuum treatment, then argon is closed, and the molten steel is subjected to standing for 20-30 min. By the adoption of the smelting process, the product rejection rate caused by large-size inclusions is reduced to be within 2%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of steelmaking process technology, and specifically relates to a method for controlling large-sized inclusions in silicon-aluminum deoxidized steel. Background Technology

[0002] Large inclusions have a significant impact on the fatigue life of steel. Large inclusions are randomly and sporadically distributed in steel, making them difficult to detect with conventional inspections, which to some extent increases the difficulty of controlling large inclusions.

[0003] The steel studied in this patent is silicon-aluminum deoxidized 45 steel, which is mainly used to produce rod-type products. It has very strict surface control requirements. Once a defect visible to the naked eye is found, the entire rod will be scrapped. Before processing, the rod needs to be machined 1.5mm on one side to remove the impact of cracks on surface quality. Therefore, the surface defects of the rod are mainly caused by large-sized inclusions.

[0004] The research results indicate that large inclusions are mainly low-melting-point CaO-containing inclusions. Literature studies such as "Behavior of CaO-containing inclusions during ladle refining of ultraclean bearing steel," "Formation mechanism of large CaO-SiO2-Al2O3 inclusions in Si-deoxidized spring steel refined by low basicity slag," "Study on formation mechanism of CaO-SiO2-based inclusions in saw wire steel," and "Formation mechanism of large-sized CaO-SiO2-CaF2-Al2O3-MgO composite inclusions in super 304H stainless steel rods," using different research methods for bearing steel, spring steel, cord steel, and 304 stainless steel, all conclude that large inclusions mainly originate from slag entrainment in refining slag. However, existing research does not provide methods to suppress slag entrainment in refining slag. Therefore, it is necessary to explore a method for stably controlling large inclusions in steel, taking into account specific steel grades and process parameters. Summary of the Invention

[0005] In view of this, based on the shortcomings of existing processes, this invention proposes a method for controlling large-size inclusions in silicon-aluminum deoxidized steel, aiming to improve the control level of large-size inclusions and reduce the product scrap rate.

[0006] The applicant analyzed the surface defects of the product ( Figure 1 The study found that the inclusions were mainly caused by large-sized inclusions, which were classified into four categories: the first category was slag entrainment in the mold mold protective slag; the second category was nodule deposits at the nozzle; the third category was refractory material spalling; and the fourth category was large-sized low-melting-point CaO-containing inclusions. Large-sized low-melting-point CaO-containing inclusions accounted for over 90% of these four categories, and they primarily originated from refining slag. The results indicate that the interfacial tension between the refining slag and molten steel is a crucial factor affecting the degree of slag entrainment; the lower the interfacial tension, the more easily the refining slag entrains. Meanwhile, the oxidizing properties of refining slag and the reactivity between refining slag and molten steel have a significant impact on interfacial tension. Specifically, the higher the oxidizing properties of refining slag and the stronger the reactivity between refining slag and molten steel (influencing factors include the desulfurization rate of refining slag on molten steel and the Al content of the molten steel itself), the smaller the interfacial tension. At this time, refining slag is more likely to be entangled. Therefore, the refining process should focus on controlling the oxidizing properties of refining slag and the reactivity between refining slag and molten steel.

[0007] This invention provides a method for controlling large inclusions in silicon-aluminum deoxidized steel. The method employs a BOF-LF-RH-CC process for smelting. The converter tapping process utilizes aluminum blocks and ferrosilicon deoxidation. After tapping, a slag-removing process is used to remove highly oxidizing slag, followed by the addition of highly reducing pre-melted refining slag to re-form the slag, ensuring that the refining slag (TFe+MnO) content remains below 0.50% for most of the refining process. During refining, the stirring intensity is controlled to maintain the refining slag desulfurization rate below 50%, minimizing slag entrapment. Before RH vacuum treatment, a 2mm thick sheet of iron is placed on the slag surface to prevent slag from being drawn into the immersion tube during insertion into the molten steel. After RH vacuum treatment, a soft blowing process is performed for 10-15 minutes, followed by argon gas shut off and the molten steel allowed to stand for 20-30 minutes. Using this smelting process, the product scrap rate caused by large inclusions is reduced to below 2%.

[0008] Specifically, this invention provides a method for controlling large-size inclusions in silicon-aluminum deoxidized steel, employing a BOF-LF-RH-CC process for smelting, and includes the following key points: (i) A 120t converter is used for blowing. The S content of the molten steel before tapping is ≤0.008%. During the tapping process, aluminum blocks and ferrosilicon are added for deoxidation and alloying. Lime is added to form slag. After tapping, the highly oxidizing slag is removed and then pre-melted refining slag is added to form new slag.

[0009] (ii) The LF process employs SiC for full-process deoxidation of the slag surface, controlling the (TFe+MnO) content of the refining slag to below 0.50%; the argon flow rate is controlled at 200~350L / min to ensure that the desulfurization rate of the refining slag is below 50%. Simultaneously, during the refining process, the Al content is adjusted to 0.004~0.010% using aluminum wire based on the steel composition analyzed from each sample.

[0010] (iii) Before RH vacuum treatment, put iron sheet on the slag liquid surface and align the iron sheet with the immersion tube opening to ensure that the slag is not drawn into the immersion tube during the process of inserting the immersion tube into the molten steel. The RH vacuum treatment time is controlled at 20~30min. After vacuum treatment, perform soft blowing for 10~15min, then turn off the argon gas and let it stand.

[0011] (iv) The continuous casting adopts an integral submerged nozzle and is protected by argon blowing throughout the casting process. The amount of steel slag left after each heat of steel casting is controlled to be more than 5t.

[0012] The silicon-aluminum deoxidized steel of the present invention has the following composition: C: 0.42~0.48%, Si: 0.15~0.35%, Mn: 0.60~0.90%, P: <0.020%, S: <0.010%, Al: 0.003~0.008%, Cr: 0.10~0.20%, with the remainder being iron and residual elements.

[0013] This invention discloses a method for controlling large inclusions in silicon-aluminum deoxidized steel. In step (I), during the tapping process, 50 kg of aluminum blocks and 350 kg of ferrosilicon are added for deoxidation and alloying, and 300 kg of lime is added for slag formation. After tapping, the highly oxidizing slag is removed, and then 1000 kg of pre-melted refining slag is added to re-form slag. The composition of the pre-melted refining slag is CaO: 45~50%, Al2O3: 45~50%, and the remainder is impurities. The slag removal after tapping is primarily to thoroughly remove the highly oxidizing slag, and by adding a highly reducing synthetic slag, it is possible to ensure that the slag (TFe+MnO) content is quickly controlled below 0.50% in the early stages of refining.

[0014] In step (II), SiC is used for full-process deoxidation of the slag surface, combined with the slag removal process after tapping, to ensure that the refining slag (TFe+MnO) is maintained below 0.50% for most of the refining process; the stirring intensity of molten steel is controlled by the argon flow rate to ensure that the desulfurization rate of the refining slag is below 50%; the Al content of molten steel is controlled at 0.004~0.010% during the refining process, mainly because the higher the Al content of molten steel, the stronger the reactivity between molten steel and slag, and the easier it is for slag entrapment to occur. However, if the Al content of molten steel is very low, it is not conducive to the control of slag oxidation. Therefore, considering these two factors and through practical exploration, the Al content control range is determined to be 0.004~0.010%.

[0015] In step (3), the sheet metal is made of ordinary 45 steel. The sheet metal should be placed in the immersion tube opening. The sheet metal will begin to melt after about 3 to 5 minutes on the slag. The molten steel should be left to stand for 20 to 30 minutes to further purify it. This is because the previous refining control and vacuum circulation cannot completely remove large-sized inclusions from the steel. It is necessary to let the molten steel stand to further remove large-sized inclusions from the steel.

[0016] Production practice has shown that implementing the method of this invention can reduce the product scrap rate caused by large-sized inclusions to less than 2.0%, reaching the advanced level in China. Attached Figure Description

[0017] Figure 1 The image shows the morphology of large inclusions detected at the surface defects of the product. The types of inclusions, from left to right, are crystallizer protective slag, nozzle nodules, refractory spalling, and low-melting-point CaO-containing inclusions. Detailed Implementation

[0018] The present invention will be described in detail below with reference to the embodiments, but these should not be construed as limiting the scope of protection of the present invention.

[0019] Example 1

[0020] The finished steel composition is: C: 0.44%, Si: 0.31%, Mn: 0.82%, P: 0.012%, S: 0.003%, Al: 0.006%, Cr: 0.13%.

[0021] A 120t converter is used for blowing. The sulfur content of the molten steel before tapping is 0.005%. During the tapping process, 50kg of aluminum blocks and 350kg of ferrosilicon are added for deoxidation and alloying, and 300kg of lime is added for slag formation. After tapping, slag is removed, and all large pieces of slag visible to the naked eye are removed. Then, a 1000kg bag of pre-prepared pre-melted refining slag is hoisted into the ladle using an overhead crane.

[0022] The LF process uses SiC for full-process deoxidation of the slag surface, with a total SiC dosage of 240 kg. The SiC content in the 15 min, 30 min, and 45 min LF processes and the final slag (TFe+MnO) is 0.45%, 0.32%, 0.27%, and 0.38%, respectively. The Al content in the molten steel at the end of the LF process is 0.008%, and the S content is 0.002%. The desulfurization rate of the entire LF process is 40.0%.

[0023] Before inserting the RH immersion tube into the molten steel, two 2mm thick iron sheets are placed on the slag surface, with the iron sheets aligned with the tube opening. The RH high vacuum time is 27 minutes, the soft blowing time is 12 minutes, and then the argon gas is turned off and the molten steel is allowed to stand for 28 minutes.

[0024] Use a cross-sectional dimension of 220mm The molten steel is solidified in a 260mm crystallizer, and then the billet is rolled into bars with a diameter of 88mm. After passing surface and internal flaw detection, it is sent to the customer.

[0025] The furnace produced a total of 1,283 rod-type products, of which 21 had defects on the surface caused by large inclusions, resulting in a scrap rate of 1.6%.

[0026] Example 2

[0027] The finished steel composition is: C: 0.45%, Si: 0.30%, Mn: 0.81%, P: 0.010%, S: 0.004%, Al: 0.007%, Cr: 0.15%.

[0028] A 120t converter is used for blowing. The sulfur content of the molten steel before tapping is 0.006%. During the tapping process, 50kg of aluminum blocks and 350kg of ferrosilicon are added for deoxidation and alloying, and 300kg of lime is added for slag formation. After tapping, slag is removed, and all large pieces of slag visible to the naked eye are removed. Then, a 1000kg bag of pre-prepared pre-melted refining slag is hoisted into the ladle using an overhead crane.

[0029] The LF process uses SiC for full-process deoxidation of the slag surface, with a total SiC dosage of 270 kg. The slag (TFe+MnO) content at LF 15 min, 30 min, 45 min, and the end slag is 0.41%, 0.35%, 0.38%, and 0.32%, respectively. The Al content of the molten steel at the end of the LF process is 0.009%, and the S content is 0.004%. The desulfurization rate of the entire LF process is 33.3%.

[0030] Before inserting the RH immersion tube into the molten steel, two 2mm thick iron sheets are placed on the slag surface, with the iron sheets aligned with the tube opening. The RH high vacuum time is 29 minutes, the soft blowing time is 10 minutes, and then the argon gas is turned off and the molten steel is allowed to stand for 26 minutes.

[0031] Use a cross-sectional dimension of 220mm The molten steel is solidified in a 260mm crystallizer, and then the billet is rolled into bars with a diameter of 88mm. After passing surface and internal flaw detection, it is sent to the customer.

[0032] The furnace produced a total of 1,352 rod-shaped products, of which 18 had defects on the surface caused by large inclusions, resulting in a scrap rate of 1.3%.

[0033] Comparative Example 1

[0034] The finished steel composition is: C: 0.43%, Si: 0.32%, Mn: 0.80%, P: 0.018%, S: 0.003%, Al: 0.007%, Cr: 0.12%.

[0035] A 120t converter is used for blowing. The sulfur content of the molten steel before tapping is 0.005%. During the tapping process, 50kg of aluminum blocks and 350kg of ferrosilicon are added for deoxidation and alloying. Then, 300kg of lime is added for slag formation. After tapping, no slag is removed. Instead, a 1000kg bag of pre-melted refining slag is hoisted into the ladle using an overhead crane.

[0036] The LF process uses SiC for full-process deoxidation of the slag surface. The total SiC usage is 260 kg. The slag (TFe+MnO) content at LF 15 min, 30 min, 45 min, and the end slag is 1.25%, 0.83%, 0.67%, and 0.48%, respectively. The Al content of the molten steel at the end of the LF process is 0.010%, and the S content is 0.003%. The desulfurization rate of the entire LF process is 40.0%.

[0037] Before inserting the RH immersion tube into the molten steel, two 2mm thick iron sheets are placed on the slag surface, with the iron sheets aligned with the tube opening. The RH high vacuum time is 24 minutes, the soft blowing time is 10 minutes, and then the argon gas is turned off and the molten steel is allowed to stand for 26 minutes.

[0038] Use a cross-sectional dimension of 220mm The molten steel is solidified in a 260mm crystallizer, and then the billet is rolled into bars with a diameter of 88mm. After passing surface and internal flaw detection, it is sent to the customer.

[0039] The furnace produced a total of 1,317 rod-like products, of which 68 had defects on the surface caused by large inclusions, resulting in a scrap rate of 5.1%.

[0040] Comparative Example 2

[0041] The finished steel composition is: C: 0.43%, Si: 0.30%, Mn: 0.79%, P: 0.011%, S: 0.001%, Al: 0.005%, Cr: 0.11%.

[0042] A 120t converter is used for blowing. The sulfur content of the molten steel before tapping is 0.007%. During the tapping process, 50kg of aluminum blocks and 350kg of ferrosilicon are added for deoxidation and alloying, and 300kg of lime is added for slag formation. After tapping, slag is removed, and all large pieces of slag visible to the naked eye are removed. Then, a 1000kg bag of pre-prepared pre-melted refining slag is hoisted into the ladle using an overhead crane.

[0043] The LF process uses SiC for full-process deoxidation of the slag surface, with a total SiC dosage of 280 kg. The SiC content in the 15 min, 30 min, and 45 min LF processes and the final slag (TFe+MnO) is 0.47%, 0.32%, 0.22%, and 0.28%, respectively. The Al content in the molten steel at the end of the LF process is 0.007%, and the S content is 0.001%. The desulfurization rate of the entire LF process is 85.7%.

[0044] Before inserting the RH immersion tube into the molten steel, two 2mm thick iron sheets are placed on the slag surface, with the iron sheets aligned with the tube opening. The RH high vacuum time is 29 minutes, the soft blowing time is 10 minutes, and then the argon gas is turned off and the molten steel is allowed to stand for 25 minutes.

[0045] Use a cross-sectional dimension of 220mm The molten steel is solidified in a 260mm crystallizer, and then the billet is rolled into bars with a diameter of 88mm. After passing surface and internal flaw detection, it is sent to the customer.

[0046] The furnace produced a total of 900 rod-shaped products, of which 89 had defects on the surface caused by large inclusions, resulting in a scrap rate of 9.9%.

[0047] Comparative Example 3

[0048] The finished steel composition is: C: 0.45%, Si: 0.28%, Mn: 0.81%, P: 0.019%, S: 0.004%, Al: 0.005%, Cr: 0.14%.

[0049] A 120t converter is used for blowing. The sulfur content of the molten steel before tapping is 0.007%. During the tapping process, 50kg of aluminum blocks and 350kg of ferrosilicon are added for deoxidation and alloying, and 300kg of lime is added for slag formation. After tapping, slag is removed, and all large pieces of slag visible to the naked eye are removed. Then, a 1000kg bag of pre-prepared pre-melted refining slag is hoisted into the ladle using an overhead crane.

[0050] The LF process uses SiC for full-process deoxidation of the slag surface, with a total SiC dosage of 220 kg. The SiC content in the 15 min, 30 min, and 45 min LF processes and the final slag (TFe+MnO) is 0.41%, 0.38%, 0.27%, and 0.32%, respectively. The Al content in the molten steel at the end of the LF process is 0.007%, and the S content is 0.004%. The desulfurization rate of the entire LF process is 42.9%.

[0051] The RH immersion tube is directly inserted into the molten steel for steel circulation preparation, without pre-inserting iron sheets. The RH high vacuum time is 25 minutes, the soft blowing time is 10 minutes, and then the argon gas is turned off to allow the molten steel to stand for 27 minutes.

[0052] Use a cross-sectional dimension of 220mm The molten steel is solidified in a 260mm crystallizer, and then the billet is rolled into bars with a diameter of 88mm. After passing surface and internal flaw detection, it is sent to the customer.

[0053] The furnace produced a total of 1,383 rod-like products, of which 39 had defects on the surface caused by large inclusions, resulting in a scrap rate of 2.8%.

[0054] Comparative Example 4

[0055] The finished steel composition is: C: 0.43%, Si: 0.28%, Mn: 0.83%, P: 0.010%, S: 0.005%, Al: 0.005%, Cr: 0.11%.

[0056] A 120t converter is used for blowing. The sulfur content of the molten steel before tapping is 0.008%. During the tapping process, 50kg of aluminum blocks and 350kg of ferrosilicon are added for deoxidation and alloying, and 300kg of lime is added for slag formation. After tapping, slag is removed, and all large pieces of slag visible to the naked eye are removed. Then, a 1000kg bag of pre-prepared pre-melted refining slag is hoisted into the ladle using an overhead crane.

[0057] The LF process uses SiC for full-process deoxidation of the slag surface, with a total SiC dosage of 260 kg. The slag (TFe+MnO) content at LF 15 min, 30 min, 45 min, and the end slag is 0.48%, 0.39%, 0.24%, and 0.27%, respectively. The Al content of the molten steel at the end of the LF process is 0.007%, and the S content is 0.005%. The desulfurization rate of the entire LF process is 37.5%.

[0058] Before the RH immersion tube is inserted into the molten steel, two 2mm thick iron sheets are placed on the surface of the slag, with the iron sheets aligned with the tube opening. The RH high vacuum time is 24 minutes, the soft blowing time is 14 minutes, and then the molten steel is directly hoisted to the continuous casting platform for casting.

[0059] Use a cross-sectional dimension of 220mm The molten steel is solidified in a 260mm crystallizer, and then the billet is rolled into bars with a diameter of 88mm. After passing surface and internal flaw detection, it is sent to the customer.

[0060] The furnace produced a total of 1,341 rod-like products, of which 49 had defects on the surface caused by large inclusions, resulting in a scrap rate of 3.7%.

[0061] Comparative Example 5

[0062] The finished steel composition is: C: 0.43%, Si: 0.28%, Mn: 0.81%, P: 0.011%, S: 0.004%, Al: 0.001%, Cr: 0.13%.

[0063] A 120t converter is used for blowing. The sulfur content of the molten steel before tapping is 0.007%. During the tapping process, 20kg of aluminum blocks and 350kg of ferrosilicon are added for deoxidation and alloying, and 300kg of lime is added for slag formation. After tapping, slag is removed, and all large pieces of slag visible to the naked eye are removed. Then, a 1000kg bag of pre-prepared pre-melted refining slag is hoisted into the ladle using an overhead crane.

[0064] The LF process uses SiC for full-process deoxidation of the slag surface, with a total SiC dosage of 290 kg. The slag (TFe+MnO) content at LF 15 min, 30 min, 45 min, and the end slag is 0.87%, 0.68%, 0.74%, and 0.59%, respectively. The Al content of the molten steel at the end of the LF process is 0.003%, and the S content is 0.004%. The desulfurization rate of the entire LF process is 42.8%.

[0065] Before inserting the RH immersion tube into the molten steel, two 2mm thick iron sheets are placed on the slag surface, with the iron sheets aligned with the tube opening. The RH high vacuum time is 23 minutes, the soft blowing time is 11 minutes, and then the argon gas is turned off and the molten steel is allowed to stand for 29 minutes.

[0066] Use a cross-sectional dimension of 220mm The molten steel is solidified in a 260mm crystallizer, and then the billet is rolled into bars with a diameter of 88mm. After passing surface and internal flaw detection, it is sent to the customer.

[0067] The furnace produced a total of 1,307 rod-like products, of which 84 had defects on the surface caused by large inclusions, resulting in a scrap rate of 6.4%.

[0068] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for controlling large-sized inclusions in silicon-aluminum deoxidized steel, characterized in that: The smelting process using the BOF-LF-RH-CC process includes the following steps: (1) A 120t converter is used for blowing. The S content of the molten steel before tapping is ≤0.008%. During the tapping process, aluminum blocks and ferrosilicon are added for deoxidation and alloying. Lime is added to form slag. After tapping, the slag is removed and pre-melted refining slag is added to form slag again. (2) In the LF process, SiC is used for full-process deoxidation of the slag surface, with an argon flow rate of 200~350L / min and an Al content of 0.004~0.010%; (3) Before RH vacuum treatment, place iron sheets on the slag surface to prevent the refining slag from being drawn into the impregnation tube. The RH vacuum treatment time should be controlled at 20~30min. After vacuum treatment, perform soft blowing for 10~15min, then turn off the argon gas and let it stand. (4) The continuous casting adopts an integral submerged nozzle and is protected by argon blowing throughout the casting process. The amount of steel slag left after each heat of steel casting is controlled to be more than 5t.

2. The method for controlling large-size inclusions in silicon-aluminum deoxidized steel according to claim 1, characterized in that: In step (1): the amount of aluminum blocks added is 50 kg; the amount of ferrosilicon added is 350 kg; the amount of lime added is 300 kg; and the amount of pre-melted refining slag added is 1000 kg.

3. The method for controlling large-size inclusions in silicon-aluminum deoxidized steel according to claim 2, characterized in that: The pre-melted refining slag composition is CaO: 45~50%, Al2O3: 45~50%, with the remainder being impurities.

4. The method for controlling large-size inclusions in silicon-aluminum deoxidized steel according to claim 1, characterized in that: In step (2), the Al content is adjusted using aluminum wire based on the steel composition analyzed from each sample.

5. The method for controlling large-size inclusions in silicon-aluminum deoxidized steel according to claim 1, characterized in that: In step (2), the content of refining slag (TFe+MnO) is controlled to be within 0.50%, and the desulfurization rate of refining slag is within 50%.

6. The method for controlling large-size inclusions in silicon-aluminum deoxidized steel according to claim 1, characterized in that: The sheet metal in step (3) is made of ordinary 45 steel, and the sheet metal should be placed in a position aligned with the immersion tube opening.

7. The method for controlling large-size inclusions in silicon-aluminum deoxidized steel according to claim 1, characterized in that: In step (3), the molten steel is allowed to stand for 20-30 minutes.

8. The method for controlling large-size inclusions in silicon-aluminum deoxidized steel according to claim 1, characterized in that: The composition of the silicon-aluminum deoxidized steel, by mass percentage, is as follows: C: 0.42~0.48%, Si: 0.15~0.35%, Mn: 0.60~0.90%, P: <0.020%, S: <0.010%, Al: 0.004~0.010%, Cr: 0.10~0.20%, with the remainder being iron and unavoidable impurities.

9. The method for controlling large-size inclusions in silicon-aluminum deoxidized steel according to claim 1, characterized in that: The cross-sectional dimension of the continuous casting machine in step (4) is 220mm. 260mm.

Citation Information

Cited By

  • Steel-making method of steel for piston rod

    CN122081792A